Garantia dos direitos de crianças e adolescentes no período de Pandemia do Covid 19 : uma perspectiva dos conselheiros tutelares - França, Ana Lucia dos Santos (2024)
The study is a master's thesis whose general objective was to understand the role of the Guardianship Council, as a member of the rights guarantee network, in the protection of children and adolescents victims of violence and violations of rights during the COVID pandemic. -19. And specific: identify the types of violence and violations of the rights of children and adolescents served by guardianship counselors during the pandemic; identify agents violating the rights of children and adolescents in the pandemic; describe how cases of violence and violations of the rights of children and adolescents were recorded during the pandemic; identify how the Information System for Children and Adolescents - SIPIA Guardianship Council (SIPIA CT) was implemented and its importance in recording cases; identify the work of the Guardianship Councils (CT) to guarantee the rights of children and adolescents in situations of violence/violation of rights during the pandemic and; analyze the relationship between CT and the network during the pandemic to enforce the rights of children and adolescents. The research was carried out in the CT of João Pessoa in 2 studies. The first addressed the violations of the fundamental rights of children and adolescents in the pandemic, their violating agents and sociodemographic aspects of the victims and the second focused on the CT's actions and its relationship with the Network for the protection and guarantee of rights. As instruments, a data collection protocol (study 1) and a semi-structured interview (study 2) were used, with the participation of 7 guardianship counselors from João Pessoa. The data were analyzed using the descriptive data analysis and Bardin Thematic Content Analysis methods, respectively. The results of the 2 studies revealed that: the right to freedom, respect and dignity was the most violated (47) during the Covid-19 pandemic and was expressed mainly in the form of physical violence (30); that the pandemic has increased cases of violation of the rights of children and adolescents; that the total or partial closure of network services made it difficult for the CT to operate and; that the SIPIA CT case registration platform has some obstacles that make it difficult for counselors to use and join the System.